2015
DOI: 10.1007/s11356-014-4055-5
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of multiple ozone metrics on daily mortality in a megacity of China

Abstract: Epidemiological studies have widely demonstrated association between ambient ozone and mortality, though controversy remains, and most of them only use a certain metric to assess ozone levels. However, in China, few studies have investigated the acute effects of ambient ozone, and rare studies have compared health effects of multiple daily metrics of ozone. The present analysis aimed to explore variability of estimated health effects by using multiple temporal ozone metrics. Six metrics of ozone, 1-h maximum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 29 publications
4
23
0
1
Order By: Relevance
“…The significant association between low level cold season ozone (mean level: 72.3 μg/m 3 ) and daily mortality observed in this study suggests that there is no threshold or a very low threshold in the ozone-mortality relationship in Jiangsu Province, China. In accordance with previous single city studies in China (Chen et al, 2013; Kan et al, 2008; Li et al, 2015; Liu et al, 2013; Yang et al, 2012), we found a stronger mortality effects of short-term ozone exposure in cold season than in warm season (Apr.–Sept.). This finding is also in line with multicity studies in Japan (Ng et al, 2013) and Thailand (Guo et al, 2014), but contradicts many studies in North America and Europe (Katsouyanni et al, 2009; Pascal et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The significant association between low level cold season ozone (mean level: 72.3 μg/m 3 ) and daily mortality observed in this study suggests that there is no threshold or a very low threshold in the ozone-mortality relationship in Jiangsu Province, China. In accordance with previous single city studies in China (Chen et al, 2013; Kan et al, 2008; Li et al, 2015; Liu et al, 2013; Yang et al, 2012), we found a stronger mortality effects of short-term ozone exposure in cold season than in warm season (Apr.–Sept.). This finding is also in line with multicity studies in Japan (Ng et al, 2013) and Thailand (Guo et al, 2014), but contradicts many studies in North America and Europe (Katsouyanni et al, 2009; Pascal et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…2). Consistently, recent studies in Asia revealed a significant ozone effect on daily mortality in cold or winter months in China (Chen et al, 2013; Kan et al, 2008; Li et al, 2015; Liu et al, 2013; Yang et al, 2012), Japan (Ng et al, 2013), and Thailand (Guo et al, 2014). The significant association between low level cold season ozone (mean level: 72.3 μg/m 3 ) and daily mortality observed in this study suggests that there is no threshold or a very low threshold in the ozone-mortality relationship in Jiangsu Province, China.…”
Section: Discussionsupporting
confidence: 66%
“…Keep in mind, high density of industries (steel, oil, and gas) makes Ahvaz as one of the most important emitters (Rad et al 2014). Breathing groundlevel ozone can trigger a variety of health problems including increased rates of hospital admissions, induction of respiratory symptoms, chest tightness, wheezing, congestion, bronchitis, emphysema, asthma, inflammation of airways, cardiopulmonary disease, and death (Frampton et al 2015;Li et al 2015). Furthermore, ozone induces decrements in pulmonary function, shortness of breath, coughing, and throat irritation; reduces lung function; decreases forced vital capacity; and reduces the maximal inspiratory position (Pride et al 2015;Yang et al 2012;Bell and Dominici 2008).…”
Section: Discussionmentioning
confidence: 99%
“…More coal consumption in power plants along with old technologies in governmental and private sectors have caused high concentration of pollutants which exceeded standards (Di Nardo and Laurenti 2015; Frampton et al 2015;Jane and Fanny 2015). There is a strong relationship between air pollution in megacities and both mortality and morbidity in whole population (Franklin et al 2015; Kampa and Castanas 2008;Kariisa et al 2015;Li et al 2015;Goudarzi et al 2015), in which since 1980 so many epidemiological and environmental studies based on statistical models have reported association between air pollutants and hospitalization, diseases, and even mortalities (Pope et al 2002;Lave and Seskin 2013;Norval et al 2011;PAGE 2003;Zallaghi et al 2014a). Criteria and also common air pollutants in ambient are particulate matter, ozone (O3), nitrogen dioxide (NO2), sulfur dioxide (SO2), and carbon monoxide (CO) (Peters et al 2000;Wong et al 2002;Mohammadi et al 2015;Zallaghi et al 2014c).…”
Section: Introductionmentioning
confidence: 99%
“…Due to a lack of available air monitoring data, no nationwide multicentre study has been conducted to date to investigate the ozone–mortality relationship in China. Numerous single‐city or small‐scale, multicentre, time‐series studies have shown increased risk of mortality following exposure to elevated ozone levels in Shanghai , Jiangsu , Zhengzhou , Wuhan , Guangzhou and Hong Kong .…”
Section: Introductionmentioning
confidence: 99%